Automatic assessment for engineering drawing - Goh, K.N. (2013)
Assessment of student's Engineering Drawing (ED) is always tedious, repetitive and time consuming. Image processing has been the common method to convert ED to be automatically assessed. This method is tedious as algorithms need to be developed for each shape to be assessed. Our research aims to create a software application that is able to perform automatic assessment for AutoCAD Drawing Exchange Format (DXF) files for undergraduate ED course. To achieve this goal, we have explored methods to convert DXF files into SVG format and develop a marking algorithm for the generated SVG files. The result shows that it is feasible to create software that automatically assesses ED without human intervention. Future implementation would include complex real-world ED. Â© 2013 Springer International Publishing.